PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN TERJADINYA CORPORATE FAILURE PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Wahyu Setyawati Utami; Indira Januarti (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence the effect of corporate governance characteristics like outside directors, outside ownership, audit opinion, remuneration of boards member, independent audit committee, and board size on probability of corporate failure. The population in this study consists of manufacturing companies listed in Indonesia Stock Exchange. Observation period was 2011-2012. Data was collected by using a purposive sampling method. The total number of samples is 147 companies, consist of 57 failed companies and 90 non-failed companies. The research data were analyzed with logistic regression. The empirical result of this study show that outside ownership and audit opinion are  significantly affect the probability of corporate failure. While outside directors, remuneration of boards member, independent audit committee, and board size has no effect on probability of corporate failure.